King Arthur And Amir Timur: Legend And Legacy Of Two Great Leaders (Zien Journal of Social Sciences and Humanities, 2025)
This article presents a comparative analysis of two leaders belonging to different cultures. Throughout history, certain figures stand out not only for their military strength or political influence but for the lasting legends and ideals they represent. King Arthur, the mythical ruler of Britain, and Amir Timur (also known as Tamerlane), the powerful conqueror of Central Asia, are two such figures. Though they come from vastly different worlds—Arthur from Celtic and medieval British legend, Timur from the Islamic and TurkicMongol tradition—they have both become symbols of leadership, justice, and national identity.